ESTABLISHING TECHNOLOGY ATTRIBUTES IN HYBRID HUMANITARIAN ASSISTANCE AND DISASTER RECOVERY FRAMEWORK - Surenthiran Krishnan; Norhazlina Fairuz Musa Kutty (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Humanitarian Assistance and Disaster Relief (HADR) become important part of Military Operations Other Than War (MOOTW) that has been emphasized in Malaysian’s Defence White Paper. HADR causes severe life losses, severely impact on economy, health, well-being, and environment. The main critical issue in deployment of HADR operation is the absence of technology attributes where it unable to achieve HADR resilience. Natural disasters are uncertain and unpredictable where they have been understood as part of a non-traditional security agenda. Recently, ASEAN countries have paid greater attention to HADR as a non-traditional security issue due to the tenacious devastation. Most HADR executions in ASEAN are lacking communications, situational awareness and emerging technologies in the context of Industrial Revolution (IR) 4.0. A qualitative research method on focus groups in ASEAN’s HADR is used to generate discussion using framework analysis inclusive with thematic analysis to draw insights on technology demands. This paper proposes a Hybrid HADR Framework that emphasizes the technology attributes in Sendai Framework for Disaster Risk Reduction (DRR) (2015 -2030) to enhance the effectiveness of HADR operation. Technology attributes are able to close the critical gaps in enhancing the effectiveness and efficiency of HADR operations. This framework will integrate various elements in the technology domain of both military and civilian capabilities in responding to HADR operations. This framework acknowledges that both military and civilian entities possess unique resources, expertise and logistical capabilities that can complement each other in addressing complex humanitarian crises and natural disasters by establishing technologies attributes. The key technology attributes is established based on the drawbacks of technology in ASEAN’s HADR. The technology attributes in hybrid framework uses communication, Geospatial Information Systems (GIS), remote sensing, autonomous system, early warning system and data analytics of artificial intelligence (AI) models. This hybrid HADR framework improves effectiveness in ASEAN’s HADR operations in Sendai Framework in technology domain.